Web-based progress monitoring in first grade mathematics - Martin Salaschek; Elmar Souvignier (EARLI, 2013)
The purpose of our research was to examine a web-based tool for mathematics progress monitoring in first grade. The newly developed assessment tool uses several robust indicators and curriculum-based measures forming three competences (Basic Precursors, Advanced Precursors, and Computation) to determine comprehensive early numeracy skills in regular education. 373 students completed a total of eight online tests every two or three weeks. Results indicate that delayed alternate-form reliability was adequate (rM = .78). Repeated measures analyses with post hoc comparisons were used to ascertain the sensitivity to assess learning growth. All three competences showed linear growth rates that were significant over time, but only Computation and overall scores produced dependable increases from test to test. Predictive validity was determined using two standardised school achievement tests (end of first grade, end of second grade). Results indicate high predictive validity of the first four online tests (rM = .67, rM = .66 for 6 months and 18 months prediction). Correlations with teacher ratings of their students' skills confirmed this pattern. Results from student and teacher questionnaires indicate that the students were able to conduct the tests independently and that a three-week interval was adequate for regular‑education use. Teachers stated to use the progress monitoring results diversely for classroom purposes. We conclude that the use of a web-based assessment setting with diverse measures is beneficial with respect to psychometric properties and feasibility for frequent use in regular education.